Dried matrix on paper disks: the next generation DBS microsampling technique for managing the hematocrit effect in DBS analysis. (August 2012) - Meesters, Roland JW; Zhang, Jamie; van Huizen, Nick A; Hooff, Gero P; Gruters, Rob A; Luider, Theo M
Background: The hematocrit effect is a hurdle for successful introduction of the dried blood spot (DBS) in a regulated environment. Recently, attempts were taken to overcome the hematocrit effect by whole-cut DBS analysis. This paper presents the next-generation whole-cut DBS; dried matrix on paper disks (DMPD).Results: DMPD eliminated the hematocrit effect and demonstrated better accuracy and precision than regular DBS with partial punching. Observed accuracy and precision were 6.0 and 2.3% for DMPD, respectively, and -10.4 and 17.1%, for DBS, respectively.Conclusion: The DMPD technique performed better than regular DBS by eliminating the hematocrit effect related blood volume bias. Although this effect was not observed with DMPD, a systematic error of 6.0% was detected and further technical development of DMPD could improve the performance.